FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TB PARU ANAK DI WILAYAH PUSKESMAS GARUDA KOTA BANDUNG - Febrian, Mira Ayu (LPPM BSI Bandung, 2015)
ABSTRACT - TB is an infectious disease which has long been known in the world. The disease is becoming a pretty big problem for public health, especially in developing countries like Indonesia. According to the WHO report of 2009, Indonesia ranked fifth after India, China, South Africa and Nigeria. Child TB cases in 2011 was 1,707 / 100,000 population. West Java is the province that has the most TB in children is high, that is 267 / 100,000 population. TB child will cause growth disorders, even to the death. This study aimed to determine the nutritional status, patients with a history of contact with adult TB patients and BCG immunization status in children TB history. This study used descriptive method with a population of 22 respondents history of pulmonary TB child and his parents. The sampling technique this study using total sampling. Retrieval of data obtained by the study of documentation, questionnaires, and observations by using univariate data processing percentages. Research results that the nutritional status of almost half of the respondents including good nutrition (40.9%) and malnutrition (36.4%), and a small proportion of respondents (22.7%) including malnutrition. Patients with a history of contact with adult TB patients most respondents (72.7%) had a positive contact history, and nearly half of the respondents (27.3%) had a history of negative contact. Then, BCG immunization status almost all respondents (86.4%) had a positive immunization status, and a small proportion of respondents (13.6%) had a negative immunization status. The conclusion that the nutritional status of almost half of the respondents nourished and malnourished. Contact history the majority of respondents have a positive contact history. BCG immunization status then almost all respondents have a positive immunization status.Keywords: Nutritional status, contact history, BCG immunization, Tuberculosis ChildrenABSTRAK - TB merupakan penyakit infeksi yang telah lama di kenal di dunia. Penyakit ini menjadi masalah yang cukup besar bagi kesehatan masyarakat, terutama di negara berkembang seperti Indonesia. Menurut laporan WHO 2009, Indonesia menduduki peringkat kelima setelah India, Cina, South Afrika dan Nigeria. Kasus TB anak pada 2011 adalah 1.707/100.000 penduduk. Jawa Barat merupakan provinsi yang memiliki penderita TB pada anak paling tinggi, yaitu 267/100.000 penduduk. TB anak akan menyebabkan terjadinya gangguan tumbuh kembang, bahkan sampai pada kematian. Penelitian ini bertujuan untuk mengetahui status gizi, riwayat kontak penderita dengan penderita TB dewasa, dan status imunisasi BCG pada anak riwayat TB Paru.Penelitian ini menggunakan metode deskriptif dengan jumlah populasi 22 responden anak riwayat TB Paru dan orang tuanya. Teknik pengambilan sampel penelitian ini menggunakan total sampling. Pengambilan data diperoleh dengan studi dokumentasi, kuesioner, dan observasi dengan pengolahan data univariate menggunakan prosentase. Hasil Penelitian bahwa status gizi hampir setengah responden termasuk gizi baik (40,9 %) dan gizi buruk (36,4 %), dan sebagian kecil responden (22,7 %) termasuk gizi kurang. Riwayat kontak penderita dengan penderita TB dewasa sebagian besar responden (72,7 %) memiliki riwayat kontak positif, dan hampir setengah responden (27,3 %) memiliki riwayat kontak negatif. Kemudian, status imunisasi BCG hampir seluruh responden (86,4 %) memiliki status imunisasi positif, dan sebagian kecil responden (13,6%) memiliki status imunisasi negatif. Kesimpulannya bahwa status gizi hampir setengah responden berstatus gizi baik dan gizi buruk. Riwayat kontak sebagian besar responden mempunyai riwayat kontak positif. Kemudian status imunisasi BCG hampir seluruh responden mempunyai status imunisasi positif.Kata Kunci : Status Gizi, Riwayat Kontak, Imunisasi BCG, Tuberkulosis Paru Anak